Femmes influentes dans le monde hellénistique et à Rome iiie siècle av. J.-C.-ier siècle apr. J.-C. - Cogitore, Isabelle; Bielman Sánchez, Anne; Kolb, Anne (Des princes, 2021)
Queens, empresses, mothers or sisters of rulers: from the Egypt of Cleopatra to the Rome of Nero, they all played a part on the political stage. This book provides the key to understanding the role of powerful women and their relationship with power in the ancient world.